Early intervention for symptomatic youth at risk for bipolar disorder: a randomized trial of family-focused therapy. - Miklowitz, D; Schneck, C; Singh, M; Taylor, DO; George, E; Cosgrove, V; Howe, M; Dickinson, L; Garber, J; Chang, K (2013)
OBJECTIVE: Depression and brief periods of (hypo)mania are linked to an increased risk of progression to bipolar I or II disorder (BD) in children of bipolar parents. This randomized trial examined the effects of a 4-month family-focused therapy (FFT) program on the 1-year course of mood symptoms in youth at high familial risk for BD, and explored its comparative benefits among youth in families with high versus low expressed emotion (EE). METHOD: Participants were 40 youth (mean 12.3±2.8 years, range 9-17) with BD not otherwise specified, major depressive disorder, or cyclothymic disorder who had a first-degree relative with BD I or II and active mood symptoms (Young Mania Rating Scale [YMRS]>11 or Child Depression Rating Scale>29). Participants were randomly allocated to FFT-High Risk version (FFT-HR; 12 sessions of psychoeducation and training in communication and problem-solving skills) or an education control (EC; 1-2 family sessions). RESULTS: Youth in FFT-HR had more rapid recovery from their initial mood symptoms (hazard ratio = 2.69, p = .047), more weeks in remission, and a more favorable trajectory of YMRS scores over 1 year than youth in EC. The magnitude of treatment effect was greater among youth in high-EE (versus low-EE) families. CONCLUSIONS: FFT-HR may hasten and help sustain recovery from mood symptoms among youth at high risk for BD. Longer follow-up will be necessary to determine whether early family intervention has downstream effects that contribute to the delay or prevention of full manic episodes in vulnerable youth.